Hyalinizing trabecular tumour of the thyroid: fine-needle aspiration cytological diagnosis and correlation with histology. Issue 8 (19th April 2017) - Saglietti, Chiara; Piana, Simonetta; La Rosa, Stefano; Bongiovanni, Massimo
Abstract : Hyalinizing trabecular tumour (HTT) is a rare thyroid neoplasm of follicular cell origin characterised by a trabecular growth pattern and prominent intratrabecular and intertrabecular hyalinisation. These peculiar histological features allow the prompt recognition of this neoplasm in surgical specimens. However, cytological diagnosis of HTT remains elusive and misleading because of overlapping characteristics with other thyroid tumours, particularly papillary thyroid carcinoma (PTC), medullary thyroid carcinoma (MTC) and the newly described non-invasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP). Nevertheless, the proper recognition of this neoplasm on preoperative cytological preparations is important to avoid unnecessary overtreatment of this indolent lesion. A thorough review of the literature has revealed that the correct diagnosis of HTT in cytological smears is achieved in only 8% of cases. In a further 6% of cases, diagnostic doubt has been indicated. Sixty percent of published cases of HTT have been misdiagnosed as suggestive, suspicious or positive for PTC. These findings underline the difficulties of a cytological-based diagnosis of such entity. In this article we review the cytomorphological features of HTT and their correlation to histological features to provide the reader with the tools to improve diagnostic performance in the identification of HTT on preoperative cytology.